2020
DOI: 10.1039/c9ra09485g
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior and optical properties of isotactic polypropylene filled with α-nucleating agents of multilayered distribution

Abstract: Isotactic polypropylene (iPP)-based multilayered composites containing alternating layers of pure iPP and α-nucleating agents (α-NAs)-filled iPP (αPP) were fabricated through layer-multiplying co-extrusion technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Isotactic polypropylene (iPP) is one of the most widely applied thermoplastic polymers due to its desirable properties, including good mechanical properties, excellent chemical and moisture resistance, versatile processability, and low manufacturing cost [ 1 , 2 ]. It is widely used in pipes, packing materials, and separators materials [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isotactic polypropylene (iPP) is one of the most widely applied thermoplastic polymers due to its desirable properties, including good mechanical properties, excellent chemical and moisture resistance, versatile processability, and low manufacturing cost [ 1 , 2 ]. It is widely used in pipes, packing materials, and separators materials [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of thermoplastic crystallinity on optical properties revealed that the dimensions of the spherulites affect light transmission through the polymer. Transmission is higher in materials with very small spherulites, while haze is higher in parts with larger spherulites [ 15 , 17 , 18 , 19 , 20 , 21 ]. The crystalline structure can be found in two most common configurations: alpha and beta.…”
Section: Introductionmentioning
confidence: 99%
“…In order to vary the dimensions of the spherulites, nucleating and clarifying agents can be incorporated into the polymer matrix, which promote an increase in the number of crystallization active centers. Additives can also be added to speed up the crystallization process, favoring the appearance of alpha spherulites, which will be smaller and have less influence on the optical properties of the final part [ 19 ]. As a general rule, the lower the percentage of alpha crystallites, the better the optical properties of the final parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby accelerating PLLA's crystallization seems to be very significant for strengthening practical application in relevant fields. Through the exploration and comparison for many years, adding a nucleating agent is thought to be a very good way of promoting the crystallization of polymer [17,18], because a nucleating agent can reduce the surface free energy barrier toward nucleation and induce the occurance of crystallization; and this method has already widely applied in semicrystalline polymers, including polyethylene terephthalate [19] and polypropylene [20,21], to enhance their crystallization performances. Similarly, this method can also be employed in PLLA as another semi-crystalline polymer.…”
Section: Introductionmentioning
confidence: 99%